A new benzofuran compound from the resinous exudates of Commiphora myrrha. Issue 9 (3rd May 2023) - Xu, Ning; Nyamdavaa, Enkhzaya; Yu, Jiaqi; Xiao, Hua; Liu, Jinglin; Li, Shuyan; Xu, Liang
Abstract: A new benzofuran derivative, identified as myrrhain A (1 ), was isolated from the resinous exudates of Commiphora myrrha, together with the four known compounds: commipharane (2 ), myrrhterpeniod (3 ), myrrhone (4 ), and 9-methoxymyrrhone (5 ). All structures were elucidated by NMR and MS analyses. DPPH assay of compounds 1 –5 revealed for the first time that all of them possess moderate antioxidative activity. Graphical Abstract: UF0001